2005
DOI: 10.1016/j.joca.2005.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyaluronic acid (MW 500–730kDa) on proteoglycan and nitric oxide production in human osteoarthritic chondrocyte cultures exposed to hydrostatic pressure

Abstract: These in vitro studies confirm both the protective role of HA (MW 500-730 kDa), which counteracts the IL-1beta-induced effects, and the importance of pressure on chondrocyte metabolism and morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…Statistical significance was analyzed by the unpaired t test (*p \ 0.05 vs. control group) suppression of PGE 2 production. It has been reported that HA inhibited PGE 2 production in chondrocytes [11], which is consistent with our results.…”
Section: Discussionsupporting
confidence: 94%
“…Statistical significance was analyzed by the unpaired t test (*p \ 0.05 vs. control group) suppression of PGE 2 production. It has been reported that HA inhibited PGE 2 production in chondrocytes [11], which is consistent with our results.…”
Section: Discussionsupporting
confidence: 94%
“…Studies of other inflammation‐related cellular systems also support NO production being modulated by HA depending on molecular weight, namely: IL‐1beta‐induced NO production from cartilage cells of osteoarthritic patients being decreased by HMW HA,72 nitrite concentration of synovial fluid of patients increasing as LMW‐HA also concomitantly increases in inflamed joints,73 and NO synthase induction in microglia from neonatal rats induced by 500–800 kDa HA and synergized by interferon‐gamma 74. Another report, however, says that 500–730 kDa HA suppresses IL‐1beta‐induced NO production from human osteoarthritis chondrocytes 75. Thus, there is no agreement in the literature as to the exact conditions or degree to which HA may suppress or enhance the inflammatory production of NO.…”
Section: Discussionmentioning
confidence: 99%
“…74 Another report, however, says that 500-730 kDa HA suppresses IL-1beta-induced NO production from human osteoarthritis chondrocytes. 75 Thus, there is no agreement in the literature as to the exact conditions or degree to which HA may suppress or enhance the inflammatory production of NO. Our data does not support direct enhancement of NO production from RAW 264.7 by LMW-HA, but does demonstrate a mild inhibition under existing strong inflammatory stimulation with LPS and mrIFN-c by HMW-HA.…”
Section: Discussionmentioning
confidence: 99%
“…NO inhibits biosynthesis of type II collagen at a post-translational level by activating prolyl hydroxylase and so inducing the hydroxylation of proline residues. The presence of hyaluronic acid (HA) in synovial fluid may counteract this catabolic effect by inhibiting IL-1 -stimulated NO synthesis [14]; however, the disruption of HA in OA may lead to loss of this potentially protective HA effect. The ability of NO to induce chondrocyte apoptosis, as discussed later, further impedes the process of matrix synthesis by reducing the number of resident cells potentially available to participate in cartilage maintenance.…”
Section: Effects Of No On Oa Chondrocytesmentioning
confidence: 99%